1986
DOI: 10.1128/jvi.57.2.693-696.1986
|View full text |Cite
|
Sign up to set email alerts
|

Gene coding for the late 11,000-dalton polypeptide of the Tian Tan strain of vaccinia virus and its 5'-flanking region: nucleotide sequence

Abstract: A late gene coding for a major structural polypeptide of 11,000 daltons from the Tian Tan strain of vaccinia virus was cloned. A comparison of the sequences from Tian Tan and WR strains of vaccinia virus revealed that there were differences in four nucleotides and one amino acid and that there was little homology between the 5'-flanking sequences of the late and the early genes. However, substantial homology was detected between the 5'-flanking sequences of the late genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The phenotypic changes observed in MVTT 2-GFP are related to the loss of the M1L-K2L genes in the VTT genome. Previous studies revealed that VTT displays genetic features distinct from other vaccinia viruses (Hou et al, 1985;Tsao et al, 1986). These genetic features led to distinct biological characteristics of VTT when compared to vaccinia WR strain (Fang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic changes observed in MVTT 2-GFP are related to the loss of the M1L-K2L genes in the VTT genome. Previous studies revealed that VTT displays genetic features distinct from other vaccinia viruses (Hou et al, 1985;Tsao et al, 1986). These genetic features led to distinct biological characteristics of VTT when compared to vaccinia WR strain (Fang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length sequence of the VTT genome was determined by Jin et al (1997). Based on sequence comparison, VTT displays genetic features distinct from other vaccinia viruses including the vaccinia western reserve (WR) strain (Hou et al, 1985;Jin et al, 1997;Tsao et al, 1986). In particular, unique deletions or insertions, which affect multiple genes, were identified in the restriction enzyme HindIII-C, B and A fragments.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported on the nucleotide sequence of a gene coding for the late 11,000-dalton polypeptide of the Tian Tan strain of vaccinia virus which had been used extensively in China for smallpox vaccination for over 60 years (5). Like other late promoters, the promoter of the 11KD gene (pll) ends with the sequence TAAATG (4).…”
mentioning
confidence: 99%